Health of Children Living Near Coal Ash - Clara G. Sears PhD, MS; Kristina M. Zierold PhD, MS (SAGE Publishing, 2017)
Coal ash, generated from coal combustion, is composed of small particles containing metals and other elements, such as metalloids. Coal ash is stored in open-air impoundments, frequently near communities. The objective of this study was to evaluate the prevalence of health and sleep problems in children living near coal ash and compare these prevalences to children not living near coal ash. In 2013 to 2014, we conducted a cross-sectional survey in a community adjacent to coal ash storage sites and a community not exposed to coal ash. Overall, 111 children who lived near coal ash were in the study; 55.9% (62) were males, 44.1% (49) were females, and the mean age was 10.3 years (SD = 3.9). Descriptive statistics and logistic regression were used to compare the prevalence of health and sleep problems. Attention-deficit hyperactivity disorder ( P = .02), gastrointestinal problems ( P = .01), difficulty falling asleep ( P = .007), frequent night awakenings ( P < .001), teeth grinding ( P = .03), and complaint of leg cramps ( P < .001) were significantly greater in the children living near coal ash. When adjusting for covariates, the odds of allergies excluding asthma, attention-deficit hyperactivity disorder, gastrointestinal problems, difficulty falling asleep, frequent night awakenings, sleep talking, and complaint of leg cramps were greater in children living near coal ash compared to children not living near coal ash (nonexposed). Several components of coal ash, such as heavy metals like lead, mercury, and arsenic, may be associated with health and sleep problems in children. More research is needed to investigate this relationship.